On the limitations of recent lawsuits against Sci‐Hub, OMICS, ResearchGate, and Georgia State University - Manley, Stewart (Wiley, 2019)
Key points The 2017 Sci-Hub judgement has, to date, proven unenforceable, and it appears that enforcing the 2019 OMICS judgement will similarly prove challenging. Business developments and changing expectations over sharing digital content may also undermine the impact of the ongoing cases against ResearchGate and Georgia State University. Stakeholders should consider these limitations when deciding how to resolve scholarly publishing disputes. © 2019 The Author(s). Learned Publishing © 2019 ALPSP.